KARAKTERISTIK FISIS PEMANCARAN CAHAYA KUNANG - KUNANG TERBANG (Pteroptyx Tener) - Melfita Sari (Department of Physics – Universitas Negeri Padang UNP, 2014)
In the city of Padang area Sungai Lareh discovered species of fireflies Pteroptyx tener. At the fireflies information about the physical characteristics of the light transmitting species is unknown. This information is essential for many applications especially in the field of bioluminisensi. Therefore carried out research with the aim of assessing the physical characteristics of the light transmitting fireflies, covering the wavelength of light emitted at maximum intensity, the decay constant, the value of the quantum yield, the number of photons emitted per second and the activation energy. This kind of research is ex post facto reveal the physical characteristics of transmitting light of fireflies and no treatment on the object under study. To obtain the data in this study using a measuring instrument that is light emission intensity: UV-VIS spectrophotometer. Fireflies used are taken from the Sungai Lareh koto Tangah Padang. The result is the value of the wavelength of maximum relative intensity is 540 nm. This value is at the wavelength of visible light with a greenish yellow color. These results are consistent with the observation that the color of light emitted by fireflies the yellow-green color. Konsatanta decay resulting from fireflies obtained at 0.0046 quanta per second, and the number of photons emitted per second by fireflies (Pteroptyx tenner) is equal to 9.93209 x 1011 quanta/second. the value of these photons can be obtained quantum yield is 0.56819. Keywords: Bioluminisensi, the fireflies, the wavelength at maximum intensity, quantum yield and activation energy.